Gender, Management Style, and the Flexibility of Informal Sector Enterprises in The Period of Covid-19: The Case of Agri-Food Microenterprises in Mali - Sanogo, Noufou; Sall, Fatou Diop (Journal of Comparative International Management)

(untitled) (Management Futures, 2023)
As in any organization, microenterprises owe their survival to their ability to adapt to changes in their environments. Informal microenterprises in Mali, particularly those run by women, also have to deal with the economic upheaval caused by the Covid-19 pandemic. This research is exploratory and aims to understand the adaptation of informal microenterprises run by women in a crisis context. To do so, a multiple case analysis is conducted. The results reveal the flexibility factors of the actions undertaken by informal women entrepreneurs to face the Covid-19 crisis. The perseverance of these women and their management style based on relational skills, as well as their mastery of the culinary arts linked to their role of "expert of the kitchen" in Malian society allowed their business to adapt to the context of the crisis. In addition to these individual characteristics and socio-cultural factors, women entrepreneurs adopted strategies such as adjusting working hours and diversifying into new activities. This research contributes to the literature by highlighting the combined effect of individual factors, gender-related socio-cultural factors, and management style on microenterprise flexibility in times of crisis.